The hybrid method for finding the roots of a polynomial over finite fields based on affine expansion - Pham Khac Hoan; Nguyen Tien Thai; Lai Tien De; Vu Son Ha (Journal of Military Science and Technology, 2023)
This paper proposes a hybrid method to find the roots of a polynomial in a finite field based on combining the polynomial decomposition into the sum of multiples of the affine polynomial with the analytical method to find the roots of low-order polynomials. The proposed method allows a significant reduction in complexity and is applicable in the design of low-latency BCH and Reed-Solomon decoders.